Extractivism as rebordering: Dmitrii Savochkin's Mark Sheider, Russo-Ukrainian mining literature, and the fragmentation of post-Soviet Ukraine. Issue 3 (4th March 2021) - Rogatchevski, Andrei
ABSTRACT: This essay examines the Russian-language novel Mark Sheider (2009) by the Ukrainian author Dmitrii Savochkin in the context of the classical American and European (Émile Zola, Upton Sinclair, George Orwell), as well as Russo-Ukrainian (Aleksandr Kuprin, Larisa Reisner, Vasilii Grossman, Boris Gorbatov, Fridrikh Gorenshtein) writing about mining. It identifies some topoi common to mining fiction and non-fiction. It also considers the Russo-Ukrainian versions of such topoi, with a special focus on extractivism represented as a form of rebordering. Wolfgang Iser's concept of fictional representation provides the article with the principal theoretical framework for the analysis.